2022
DOI: 10.21203/rs.3.rs-1676011/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Controlling Diastereodivergent Light-Driven Processes: The Impact of the Light Source and Steric Factors on the Paternò-Büchi Reaction

Abstract: By conducting in-depth mechanistic investigations to rationalize reaction manifolds, chemists can expand the generality of synthetic processes and discover novel reactivities. The challenge is to use the resulting information to control the selectivity of a given synthetic process. A particular challenge for organic chemists is to use an external stimulus to switch a reactivity on or off. Here, we mechanistically investigated light-driven [2+2] heterocycloadditions (Paternò-Büchi reactions) between indoles and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In 2022, Dell'Amico and co-workers conducted indepth research on the mechanism of light-driven Paternò-Büchi reaction involving diketone compound and indole derivatives, which was based on photodynamic analyses, TAS experiments and DFT calculations (Scheme 5). [15] The mechanistic studies indicated that the reaction undergo two different pathways, exciplex and EDA complexes, which were two key intermediates leading to the opposite diasteroisomeric form of oxetane products.…”
Section: Direct Sensitization For Paternò-büchi Reactionmentioning
confidence: 99%
“…In 2022, Dell'Amico and co-workers conducted indepth research on the mechanism of light-driven Paternò-Büchi reaction involving diketone compound and indole derivatives, which was based on photodynamic analyses, TAS experiments and DFT calculations (Scheme 5). [15] The mechanistic studies indicated that the reaction undergo two different pathways, exciplex and EDA complexes, which were two key intermediates leading to the opposite diasteroisomeric form of oxetane products.…”
Section: Direct Sensitization For Paternò-büchi Reactionmentioning
confidence: 99%